Community Involvement and Sustainable Cave Tourism Development in Tulungagung Region - ALY, M. Nilzam; HAMID, Nur; SUHARNO, Novianto Edi; KHOLIS, Nor; AROYANDINI, Elvara Norma (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).28, 2021)
The model was focusing on the community involvement of tourism activities based on rural collaborative-construction with the different ways to utilize at Tenggar Cave, Tenggarrejo Village, Tulungagung region in order to ensure the sustainability ofheritage tourism development in that area. A qualitative approach through participating observation, indepth interviews, study of document and focus group discussions were obtained to reliability and validity data. Interviews were conducted to informants of the development planning agency at sub-national level, tourism government regency, Indonesian State Forest Company, the members of the local tourism community, local entrepreneur, tourist, archeology and researcher. The results indicated that local communities and other stakeholders have participated in management, conservation, tourism development of the site, solved social problems and benefit in that area such as poverty, lack of job opportunity, and corncob waste. This research suggested that collaboration model which was developed within the tourism planning must implement principles of sustainable and involve full role of the local community. Community Based Heritage Management (CBHTM) is an ideal model in the development of tourism in the Tenggar Cave area.